Pengaruh Kualitas Aktiva Produktif, CAR, Leverage dan LDR Pada Profitabilitas Bank - Triana Dewi, Nyoman; Suparta Wisadha, I Gede (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
The aim of this research was to know the effect of assets quality, capital adequency ratio, leverage and loan to deposit ratio towards profitability of bank listed on stock exchange period 2008-2012. This research had 9 samples of bank company which choosen by purposive sampling technic. This research used multiple linier regression analysis. The result found assets quality and CAR had no effect on the profitability. This suggests that bank pay less the assets quality and CAR to keep the profitability. The result found leverage and LDR had a negative effect on profitability. This suggests that the higher value of leverage and LDR in bank profitability will decline.
Keywords: assets quality, capital adequency ratio, leverage, loan to deposit ratio, profitabilitas